The ownership and clinical use of smartphones by doctors and nurses in the UK: a multicentre survey study. Issue 4 (7th October 2015) - Mobasheri, Mohammad H; King, Dominic; Johnston, Maximilian; Gautama, Sanjay; Purkayastha, Sanjay; Darzi, Ara
Abstract : Background: Much interest has arisen around the use of smartphones, tablet devices and related apps in the healthcare context. It has been suggested that increasing numbers of healthcare professionals are using these technologies in the workplace. We have performed an up-to-date UK-based, multicentre, cross-sectional survey study exploring the ownership rates and uses of these technologies among doctors and nurses, specifically focusing on the clinical environment. Methods: After initial piloting, all doctors (n=2107) and nurses (n=4069) at 5 hospital sites were invited to complete a 36-item (nurses) or 38-item (doctors) survey. Exploratory descriptive statistics were calculated and the χ 2 test was used to compare differences in categorical data between groups. Statistical significance was taken at a level of p<0.05. Results: 98.9% of doctors and 95.1% of nurses owned a smartphone, while 73.5% and 64.7% owned a tablet device, respectively. Also, 92.6% of the doctors and 53.2% of nurses found their smartphone to be 'very useful' or 'useful' in helping them to perform their clinical duties, while 89.6% of doctors and 67.1% of nurses owning medical apps were using these as part of their clinical practice. Doctors and nurses were using short-message-script messaging (64.7% and 13.8%, respectively), app-based messaging (33.1% and 5.7%), and picture messaging (46.0% and 7.4%) (p=0.0001 for all modalities) to send patient-related clinical information to their colleagues. Therefore, 71.6% of doctors and 37.2% of nurses wanted a secure means of sending such information. Conclusions: Compared to earlier studies, we have demonstrated much higher smartphone ownership among doctors and nurses, who perceive these devices to be useful when performing their clinical duties. Large numbers of staff are sending patient related clinical information using smartphone messaging modalities. Care must be taken by doctors and nurses to ensure that no identifiable patient data is transmitted in this way, and healthcare organisations must develop strategies and policies to support the safe and secure use of these technologies by front-line staff.